Theorems on instability of systems with respect to linear approximation - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of instability of solutions of differential equations with a stationary linear part and a nonstationary nonlinear compact part in a Banach space.